Review of advanced wdm techniques for spectral efficiency in optical communication networks - Santillan Carranza, Holger (2025)
This paper presents the analysis of wavelength division multiplexing (WDM) in fiber optic networks (FTTH) with the objective of optimizing the quality of service to the customer. An FTTH network with WDM was designed and simulated using OptiSystem software. Subsequently, the configuration was experimentally validated with equipment from a GPON network of the optical communications laboratory. Measurements were performed with different wavelengths and powers to evaluate the multiplexing efficiency. The results showed that the 1490 nm wavelength with a power of -82.737 dB proved to be the most efficient, with a prototype efficiency of 87.5%. The simulation in OptiSystem yielded a value of -76.471 dB, indicating that the simulation does not accurately reflect the results of the WDM technique in practice. This work validates the WDM technique as a viable solution to improve the quality of service in FTTH networks. A precedent was established for future research using a GPON model and the WDM technique in different telecommunication scenarios.